3D printing based on imaging data: review of medical applications - Rengier, Fabian; Mehndiratta, A.; Tengg-Kobligk, Hendrik von; Zechmann, C. M.; Unterhinninghofen, R.; Kauczor, Hans-Ulrich; Giesel, Frederik L. (International journal of computer assisted radiology and surgery, 2010)
Purpose: Generation of graspable three-dimensional objects applied for surgical planning, prosthetics and related applications using 3D printing or rapid prototyping is summarized and evaluated. Materials and methods: Graspable 3D objects overcome the limitations of 3D visualizations which can only be displayed on flat screens. 3D objects can be produced based on CT or MRI volumetric medical images. Using dedicated post-processing algorithms, a spatial model can be extracted from image data sets and exported to machine-readable data. That spatial model data is utilized by special printers for generating the final rapid prototype model. Results: Patient–clinician interaction, surgical training, medical research and education may require graspable 3D objects. The limitations of rapid prototyping include cost and complexity, as well as the need for specialized equipment and consumables such as photoresist resins. Conclusions: Medical application of rapid prototyping is feasible for specialized surgical planning and prosthetics applications and has significant potential for development of new medical applications.
Gesehen am 12.05.2023